Sistem Pendukung Keputusan Menentukan Kepala Peneliti Pada Riset Pengembangan Tebu Dan Tembakau Deli (RTT) Sampali Menggunakan Metode Promethee II - Yeni Ramadhani; Maringan Sianturi (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
The decision support system is a computer-based system consisting of components, including language system components, knowledge system components and problem processing system components that interact with one another. Decision support system is an interactive system, which helps decision makers through the use of data and decision models to solve semi-structured and unstructured problems. Promethee is a method of determining the order or priority in MCDM (Multi Criterion Decision Making) or multiple criteria decision making which is a very important discipline in making decisions on a problem that has more than one criteria (Multi Criteria). The decision support system using the promethee method is able to analyze the criteria and alternatives being compared. The results showed that the use of promethee as a decision support system to determine the head of the researcher at the Deli Sugarcane and Tobacco Development Research (RTT) Sampali could assist the company in determining the head of the researcher with a faster and more effective multi-work weighting and selection process